Social geographies from difference to action - Panelli, Ruth (SAGE, 2004)
This accessible textbook is a stimulating introduction to contemporary social geography. It provides students with the tools to understand the various frameworks that geographers use to conceptualize, document, and attempt to overcome social differences
Literaturangaben und Index
Neue Seitenzählung in jedem Kapitel, abweichend von Seitenzählung in print-Version
Keywords: Social geography; Social geography -- Methodology; Sozialgeografie; Einführung